Cover Feature: Toxin‐Blocking Textiles: Rapid, Benign, Roll‐to‐Roll Production of Robust MOF‐Fabric Composites for Organophosphate Separation and Hydrolysis (ChemSusChem 2/2023). Issue 2 (3rd January 2023) - Morgan, Sarah E.; Willis, Morgan L.; Dianat, Golnaz; Peterson, Gregory W.; Mahle, John J.; Parsons, Gregory N.
Abstract : The Cover Feature shows rapid, roll‐to‐roll synthesis of metal–organic framework fabric composites utilizing low boiling point, environmentally conscious solvents. The metal–organic framework fabrics neutralize chemical warfare agents and block toxin permeation. More information can be found in the Research Article by S. E. Morgan et al .